Dimensional Context of Total Quality Management Practices and Organizational Performance of SMEs in Nigeria: Evidence from Mediating Role of Entrepreneurial Orientation - Olaleye, Banji Rildwan; Ali-Momoh Betty, Oluwayemisi Oluwayemisi; Herzallah, Ahmad M.; Sibanda, Nomazwe; Ahmed, Aminat Favour (International Forum of Management Scholars, 2021)
This paper aims to explore the nexus between Total Quality Management practices and Organizational Performance, and the mediating effect of the Entrepreneurial Orientation dimension on the relationship. A cross-sectional data was obtained from 549 small-scale manufacturing companies using convenience sampling. Data were analyzed using both descriptive and inferential techniques. Discovery unveiled through the PLS-SEM result, shows a tie of relationship existing between TQM and performance, as well as entrepreneurial orientation dimension. Since, firms had a high capacity for innovativeness, proactiveness, and risk-taking; they acquire a competitive advantage and realize greater performance. © 2021, International Forum of Management Scholars. All rights reserved.
Keywords: Entrepreneurial Orientation; Organizational Performance; PLS-SEM; TQM